2015
DOI: 10.1021/jp510272s
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence of A100 MOF and Adsorption of Water, Indole, and Naphthalene on A100 by the Spectroscopic, Kinetic, and DFT Studies

Abstract: Metal−organic frameworks (MOFs) are promising materials for adsorption and separations. It is important to understand the details of chemical bonding between the adsorbate and structural units in the MOFs. In A100 MOF, the near-UV− visible fluorescence is found to be the intralinker fluorescence. Naphthalene and indole form the stoichiometric "host-guest" π−π adsorption complexes with A100 that contain one adsorbate molecule per two BDC linkers, and adsorption of indole causes a strong quenching of the intrali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…In addition, analysis of the temperature prole allowed us to estimate the kinetics of water adsorption, which is rarely explored. 55 Analysis of adsorption peaks shows that under the current experimental conditions, the temperature curve reaches a base temperature aer 1400 s, while complete desorption of water from the pores occurs aer 2100 s of purging with dry nitrogen gas (Fig. 6a).…”
Section: Characterisation Of the D 2 O-loaded Samplesmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, analysis of the temperature prole allowed us to estimate the kinetics of water adsorption, which is rarely explored. 55 Analysis of adsorption peaks shows that under the current experimental conditions, the temperature curve reaches a base temperature aer 1400 s, while complete desorption of water from the pores occurs aer 2100 s of purging with dry nitrogen gas (Fig. 6a).…”
Section: Characterisation Of the D 2 O-loaded Samplesmentioning
confidence: 90%
“…6a). 55 Multiple exposure of the adsorbent to a working uid during the lifetime of the device requires an enhanced chemical stability of the material. In previous studies, DUT-67(Zr), synthesized in DMF, was claimed as a MOF with reduced chemical stability against water and acids, 24 and therefore, we performed a comprehensive stability study on the MOF, synthesized using a "green" synthesis procedure, under normal working conditions, but also under harsh conditions, which are rather not typical for adsorption heat pumps.…”
Section: Characterisation Of the D 2 O-loaded Samplesmentioning
confidence: 99%
“…Modeling MIL-53(Al) Clusters with Three Water Molecules. In the recent experimental study, 16 we showed that Basolite A100 with framework of MIL-53(Al) adsorbs water…”
Section: Resultsmentioning
confidence: 92%
“…Recently, we successfully used the DFT with the M06-2X functional to calculate the energies and geometry of binding sites of naphthalene and indole to the MIL-53(Al) cluster. 16 In this study, we build a discrete model of the MIL-53(Al) cavity, where the large-pore and narrow-pore forms and the transition between the two can be modeled as a function of temperature. We describe the systematic DFT computations with the M06-2X functional and 6-31G(d) and LANL2DZ basis sets, as well as computations at the B3LYP-D3BJ/6-31G(d,p)//M06-2X/6-31G(d) level to investigate the MIL-53(Al) cluster with three water molecules.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation